In‐hospital outcome of peripheral vascular intervention in dialysis‐dependent end‐stage renal disease patients. Issue 3 (21st October 2019) - Moussa Pacha, Homam; Al‐khadra, Yasser; Darmoch, Fahed; Soud, Mohamad; Mamas, Mamas A.; Moussa Pacha, Abdulghani; Zaitoun, Anwar; Kaki, Amir; AlJaroudi, Wael A.; Alraies, M. Chadi
Abstract: Background: The impact of end‐stage renal disease (ESRD) on peripheral vascular intervention (PVI) outcome remains incompletely elucidated. Objectives: We sought to compare the outcome of PVI in dialysis patients with those with normal kidney function. Methods: Using weighted data from the National Inpatient Sample database between 2002 and 2014, we identified all peripheral artery disease (PAD) patients aged ≥18 years that underwent PVI. Multivariate logistic regression analysis was performed to examine in‐hospital outcomes. Results: Of 1, 186, 192 patients who underwent PVI, 1, 066, 830 had normal kidney function (89.9%) and 119, 362 had ESRD requiring dialysis (10.1%). Critical limb ischemia was more prevalent in dialysis patients (63.2 vs. 34.0%, p < .001). Compared with normal kidney function group, ESRD requiring dialysis was associated with higher in‐hospital mortality (1.5 vs. 4.2%, adjusted OR: 2.13 [95% CI: 2.04–2.23]) and longer length of hospital stay (median 3 days, Interquartile range [IQR] (0–6) vs. 7 days, IQR (4–18); p < .001). Dialysis patients had higher incidence of major adverse cardiovascular events (composite of death, myocardial infarction, or stroke; 14.3 vs. 9.8%, p < .001) and net adverse cardiovascular events (composite of MACE, major bleeding, or vascular complications; 40.8 vs. 29.1%, p < .001). ESRD patients less frequently underwent open bypass (5.6 vs. 8.5%, p < .001) and more frequently had major amputation (10.3 vs. 3.0%, p < .001) compared with normal kidney function group. Conclusion: PAD patients on dialysis who underwent PVI have higher rates of mortality and adverse outcomes as compared to those with normal kidney function.